1994
DOI: 10.1016/0035-9203(94)90402-2
|View full text |Cite
|
Sign up to set email alerts
|

Schistosomiasis in the Republic of São Tomé and Principe: human studies

Abstract: The only schistosome species found in stool specimens in the local population of the republic of São Tomé is Schistosoma intercalatum. An initial survey of schoolchildren showed an overall prevalence of 10.9%, with some schools reaching 29%. No S. haematobium egg was found in 782 urine specimens from the local population, although some were seen in the urine of Angolan soldiers stationed near the capital city. One village in the endemic area, San Marçal, had an S. intercalatum prevalence of 43%, with 14 person… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 12 publications
1
15
0
Order By: Relevance
“…However, IPIs studies in SAC are quite rare; only two studies conducted in 1987 and 2005 indicated that the prevalence of A. lumbricoides, T. trichiura, and some intestinal protozoan infections were fairly high in SAC [13][14][15][16][17] . Largely from 2005 onwards, the DRSTP accepted the advice of non-governmental organizations (NGOs) to begin SAC-based deworming program using a single-dose mebendazole regimen annually.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, IPIs studies in SAC are quite rare; only two studies conducted in 1987 and 2005 indicated that the prevalence of A. lumbricoides, T. trichiura, and some intestinal protozoan infections were fairly high in SAC [13][14][15][16][17] . Largely from 2005 onwards, the DRSTP accepted the advice of non-governmental organizations (NGOs) to begin SAC-based deworming program using a single-dose mebendazole regimen annually.…”
Section: Introductionmentioning
confidence: 99%
“…Although limited information is available regarding the IPIs status among inhabitants of the Democratic Republic of Sao Tome and Principe (DRSTP) [13][14][15][16][17] , like other developing countries, IPIs are supposedly a major health problem in the DRSTP due to tropical climatic and poor hygienic conditions. However, IPIs studies in SAC are quite rare; only two studies conducted in 1987 and 2005 indicated that the prevalence of A. lumbricoides, T. trichiura, and some intestinal protozoan infections were fairly high in SAC [13][14][15][16][17] .…”
Section: Introductionmentioning
confidence: 99%
“…In our study, M. huberti and A. niloticus released several thousands of S. intercalatum eggs per gram of Kuntz et al (1978) reported a maximal egg output of 1,310/g feces. A recent study has shown that a patient may release an average of 194 S. intercalatum eggs/g feces (Almeda et al 1994). We may thus consider that M. huberti and A. niloticus allow a high production of eggs.…”
Section: Discussionmentioning
confidence: 99%
“…Until the 1970s this disease had been established in the forest areas of Central and West Africa (Cameroon, Gabon, Zaire). For a decade, S. intercalatum has extended its distribution toward new countries: Equatorial Guinea (Corachan et al 1987), Mali (Corachan et al 1992), Nigeria (Arene et al 1989), and SaÄ o Tome (Almeda et al 1994). However, in spite of the emergence of these new foci the distribution of S. intercalatum remains restricted as compared with that of the intermediate host.…”
Section: Introductionmentioning
confidence: 99%
“…Schistosomiasis is endemic on São Tomé but absent in Príncipe [28]. Is it too much to hope that this could sometime be said for malaria on the island?…”
Section: Discussionmentioning
confidence: 99%